The Role of Data Leakage Prevention System in CBDC - Adesh Mukati; Dr. Satya Prakash, (Indian Journal of Cryptography and Network Security (IJCNS), 2024)
A centralized database-based Central Bank Digital Currency (CBDC) system’s vulnerability to cyberattacks and data leakage is a major concern. Any data leak can lead to large financial losses, irreversible reputational harm, and a decline in user confidence. To protect user information, the Reserve Bank of India has underlined the significance of a strong Data Leakage Prevention (DLP) system. While current incidents have demonstrated that the measures were insufficient to meet the standards, DLP may not be enough to defend CBDCs on its own. Incorporating Zero-Knowledge Proofs (ZKPs) and differential privacy tools into DLP solutions can improve their robustness and effectiveness. There is no one-size-fits-all solution for preventing data leakage, different solutions may be more effective in different scenarios. It’s always a good idea to assess an organization’s or system’s specific needs and requirements before deciding on the best solution. It is also important to remember that there is no such thing as absolute security, and the possibility of zero-day attacks is always there. It is essential to continuously monitor and enhance security measures to stay ahead of new threats. To preserve their Central Bank Digital Currency systems and data, financial institutions and central banks must continue to be proactive and vigilant.